Emotional Regulation as a Remedy for Teacher Burnout in Special Schools: Evaluating School Climate, Teacher’s Work-Life Balance and Children Behavior - Mulyani, Sri; Salameh, Anas A.; Komariah, Aan; Timoshin, Anton; Hashim, Nik Alif Amri Nik; Fauziah, R. Siti Pupu; Mulyaningsih, Mulyaningsih; Ahmad, Israr; Ul din, Sajid Mohy (Frontiers in Psychology, 2021)
This research aimed to identify whether improvement in working conditions, children’s classroom behaviour and work-life balance can lower teacher burnout ratio in Pakistan’s special schools by using techniques such as emotions regulation. The researcher employed a quantitative research methodology to fulfil the research’s purpose. The data for this research was collected using a questionnaire-based instrument. The confirmatory factor analysis and structural equation modelling techniques were used to test the construct validity and underlying structural relationships. The findings demonstrated that the impacts of all three variables are significant in reducing job burnout in teachers. Emotional regulation helps decrease the impact of working conditions and the children’s behaviour. Nevertheless, it does not aid work-life balance as it requires other techniques of emotional regulation. The research is significant as it highlights the importance of overall working conditions’ improvement for teachers working with special needs children. The improvements are essential because the teachers must take extra effort and emotions into their job compared to a typical teacher. The researcher has highlighted the key finding, implications and limitations of this research besides suggesting directions for future research to facilitate peer researchers.